Non-hospital healthcare center's preparedness assessment toolbar for providing basic emergency care: a sequential exploratory mixed-method study - Homayoun Sadeghi-Bazargani; Mehrdad Amir-Behghadami; Ali Janati; Farzad Rahmani (BMC, 2023)
Abstract Background Basic emergency management in urban and rural areas is a critical challenge, which can affect the pre-hospital mortality rate. Therefore, Non-hospital Healthcare Center (NHHC) must be prepared to manage such emergency cases that may occur in the geographic area where these centers act. The main aim of the study was to develop and validate an toolbar for NHHCs' preparedness to provide initial emergency care. Methods This study was designed based on a sequential exploratory mixed- method in two phases, in each of which there are three steps. In the phase I, the literature systematic review and qualitative methods (Focus Group Discussions (FGDs) and Semi-Structured Interviews (SSIs)) were applied to identify the domains and items. In the phase II, content validity, feasibility, and reliability of the toolbar were performed. Content validity was assessed using a modified Kappa coefficient based on clarity and relevance criteria. Feasibility of the toolbar was randomly assessed through its implementation in 10 centers in Tabriz. Reliability was randomly assessed in a pilot on 30 centers. Reliability was assessed by measuring internal consistency, test-retest reliability, and inter-rater agreement. The main statistical methods for assessing reliability include Cronbach's alpha, Intra-class Correlation Coefficient, and Kendal's Tau-b. All the statistical analyses were performed using Stata 14. Results In the phase I, primary version of the toolbar containing 134 items related to assessing the preparedness of NHHCs was generated. In the phase II, item reduction was applied and the final version of the toolbar was developed containing 126 items, respectively. These items were classified in 9 domains which include: "Environmental Infrastructures of Centers", "Protocols, Guidelines and Policies", "Medical Supplies and Equipment", "Emergency Medicines", "Human Resources", "Clinical Interventions", "Maintenance of equipment", "Medicine Storage Capability", and "Management Process". The toolbar had acceptable validity and reliability. Conclusions This study provided a standard and valid toolbar that can be used to assess the preparedness of NHHCs to deliver initial emergency care.